2017
DOI: 10.1080/0284186x.2017.1346382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PET and CT radiomics for prediction of local tumor control in head and neck squamous cell carcinoma

Abstract: (2017). Material and methodsData from HNSCC patients (n=121) treated with definitive radiochemotherapy were used for model training. In total, 569 radiomic features were extracted from both contrast enhanced CT and 18F-FDG PET images in the primary tumor region.CT, PET and combined PET/CT radiomic models to assess local tumor control were trained separately. Five feature selection and three classification methods were implemented. The performance of the models was quantified using concordance index (CI) in 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
104
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 23 publications
8
104
1
Order By: Relevance
“…In total, 1404 features were extracted per patient/image (see Supplementary Tables 1-4). The definitions of analyzed intensity and texture features are described by Zwanenburg et al [16], whereas the details on implementation of the shape features and the wavelet transform can be found in work by Bogowicz et al [17,18]. For intensity, texture and wavelet analysis images were resized to cubic voxels of 3 mm for NSCLC, 2 mm for HNSCC and 3.3 mm for MPM using linear interpolation.…”
Section: Radiomics Analysis and Image Pre-processingmentioning
confidence: 99%
“…In total, 1404 features were extracted per patient/image (see Supplementary Tables 1-4). The definitions of analyzed intensity and texture features are described by Zwanenburg et al [16], whereas the details on implementation of the shape features and the wavelet transform can be found in work by Bogowicz et al [17,18]. For intensity, texture and wavelet analysis images were resized to cubic voxels of 3 mm for NSCLC, 2 mm for HNSCC and 3.3 mm for MPM using linear interpolation.…”
Section: Radiomics Analysis and Image Pre-processingmentioning
confidence: 99%
“…To date, in vivo disease characterization with hybrid imaging data-especially in the light of oncological applications-is performed mainly by analyzing engineered features [63,129]. This process is widely referred to as "Radiomics, " even though, this kind of approach was originally applied to morphological images only [8].…”
Section: Joint Data Explorationmentioning
confidence: 99%
“…There is increasing evidence for in vivo tissue characterization with both PET/CT and PET/MRI hybrid imaging [11,146,174,175]. In one study, PET, CT, and PET/CT features were used to predicting local tumor control in head and neck cancer [129] by multivariate cox regression with a confidence interval (CI) CI CT and CI PET/CT of 0.73, however, CT-based radiomics overestimated the probability of tumor control in the poor prognostic groups. Another study found a correlation of PET and CT features using lymph node density [176] and concluded that CT density measurements together with PET uptake analysis increases the differentiation between malignant and benign LN.…”
Section: Radiomicsmentioning
confidence: 99%
“…This result was strongly consistent with those of previous studies. 22,26,27 Among all the 10 features, most of them were higherorder statistics features and utilised wavelet transform. Higher-order statistics features could display subtle alterations in tissue morphology more explicitly.…”
Section: Discussionmentioning
confidence: 99%